Influence of Spin Coating and Dip Coating with Gelatin/Hydroxyapatite for Bioresorbable Mg Alloy Orthopedic Implants: In Vitro and In Vivo Studies - Tran, Duong-Thuy; Chen, Fang-Hsu; Wu, Guan-Lin; Ching, Paula Carmela O.; Yeh, Ming-Long (ACS biomaterials science & engineering, 2023)
Suitable biomechanical properties, good biocompatibility, and osteoconductivity of a degradable magnesium (Mg) alloy make it a potential material for orthopedic implants. The main limitation of Mg is its high corrosion rate in the human body. Surface modification is necessary to improve the Mg corrosion resistance. In this work, a polymeric layer of gelatin/nanohydroxyapatite (Gel/nHA) was coated on a ZK60 Mg alloy by dip coating and spin coating to test the corrosion resistance and biocompatibility in vitro and in vivo. The results from the in vitro test revealed that the coated groups reduced the corrosion rate with the corrosion current density by 59 and 81%, from 31.22 to 12.83 μA/cm2 and 5.83 μA/cm2 in the spin coating and dip coating groups, respectively. The dip coating group showed better corrosion resistance than the spin coating group with the lowest released hydrogen content (17.5 mL) and lowest pH value (8.23) and reducing the current density by 45%. In vitro, the relative growth rate was over 75% in all groups tested with MG63, demonstrating that the Mg substrate and coating materials were within the safety range. The dip coating and spin coating groups enhanced the cell proliferation with significantly higher OD values (3.3, 3.0, and 2.5, respectively) and had better antihemolysis and antiplatelet adhesion abilities than the uncoated group. The two coating methods showed no difference in the cellular response, cell migration, hemolysis, and platelet adhesion test. In in vivo tests in rats, the dip coating group also showed a higher corrosion resistance with a lower corrosion rate and mass loss than the spin coating group. In addition, the blood biochemistry and histopathology results indicated that all materials used in this study were biocompatible with living subjects. The present research confirmed that the two methods have no noticeable difference in cell and organ response but the corrosion resistance of dip coating was higher than that of spin coating either in vitro or in vivo.